Lextutor English Learning Pronunciation and Vocabulary: A Language Data Base Program - Bonar Siagian; M Bambang Purwanto (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
The aim of this research is to highlight the role of Lextutor an online software for achieving educational objectives. Lextutor is an online resource which presents a new teaching-learning environment and also offers a variety of activities for educators and learners to use it in English vocabulary classroom and to nurture independent learning. Since vocabulary becomes very fundamental in language learning, both speaking and writing and independent learning is currently popular and needs to be developed, educators and learners can use wordlists, online concordance and dictionary, and texts, which can be accessed in the available programs. In addition, Lextutor also serves database to store the work and view the others’ work. Most importantly, this online software comes up with the transformation to change the traditional setting of learning by giving inputs on DDL learning. It is expected that learners can be more independent and active in learning, enabling greater motivation and deeper learning. This paper reviews literature and gives scholarly background by reviewing some contributions and concepts made by experts in the related field. Furthermore, some benefits of using Lextutor are found in this research.